Trends in blood lead levels in UK workers, 1995–2007. Issue 9 (26th August 2010) - Morton, Jackie; Cotton, Richard; Cocker, John; Warren, Nicholas D
Abstract : Objectives: This study evaluated blood lead data (including zinc protoporphyrin (ZPP) and haemoglobin levels) collected at the UK's Health and Safety Laboratory (HSL) in order to determine temporal changes in occupational exposure to lead between 1995 and 2007. Methods: A total of 20 889 blood lead measurements and accompanying ZPP and haemoglobin results from 8810 workers at 972 companies from routine samples received by HSL over the period 1995–2007 were analysed. Time trends in blood lead levels for each industry sector were estimated using Bayesian mixed effects modelling. Results: Reductions in median blood levels over the period 1995–2007 were seen in every sector except for those samples forwarded by occupational health providers, and range from 1.6% per year for workers in the smelting industry to 12% per year for workers in pottery and glazing industries. An overall reduction of 3.1% per year across all industries was determined. The percentage of results above the current UK suspension limit of 60 μg/dl fell from 4.8% in 1995 to 0.6% in 2007. ZPP and blood lead exhibited a strong association, but no significant correlation was found between blood lead and haemoglobin. Conclusions: Occupational exposure to lead has fallen across UK industries in recent years, although it remains substantially above background levels. There is evidence that many workers are exposed to elevated lead levels over a long period of time and this deserves renewed consideration now that inorganic lead has been reclassified as a probable human carcinogen.